1998
DOI: 10.1017/s0140525x98001174
|View full text |Cite
|
Sign up to set email alerts
|

Linear correlates in the speech signal: The orderly output constraint

Abstract: Neuroethological investigations of mammalian and avian auditory systems have documented species-specific specializations for processing complex acoustic signals that could, if viewed in abstract terms, have an intriguing and striking relevance for human speech sound categorization and representation. Each species forms biologically relevant categories based on combinatorial analysis of information-bearing parameters within the complex input signal. This target article uses known neural models from the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 174 publications
2
103
0
1
Order By: Relevance
“…To the extent that patterns of covariance among acoustic attributes in natural sounds are efficiently coded, these non-isomorphic representations may inform how the auditory system exploits different patterns of redundancy to learn to distinguish different speech sounds. For example, extraction of relational properties across variations consequent to coarticulation (e.g., locus equations, Sussman et al, 1991Sussman et al, , 1998 or anatomy (scaling of formant frequencies across changes in vocal tract length across talkers, Kluender et al, 2011) are the most direct speech analogs to non-isomorphism demonstrated here. In related studies employing fMRI, Okada et al (2010) report that responses in bilateral posterior superior temporal sulcus were sensitive to phonemic variability (intelligibility) of speech sounds, but not to acoustic variability.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…To the extent that patterns of covariance among acoustic attributes in natural sounds are efficiently coded, these non-isomorphic representations may inform how the auditory system exploits different patterns of redundancy to learn to distinguish different speech sounds. For example, extraction of relational properties across variations consequent to coarticulation (e.g., locus equations, Sussman et al, 1991Sussman et al, , 1998 or anatomy (scaling of formant frequencies across changes in vocal tract length across talkers, Kluender et al, 2011) are the most direct speech analogs to non-isomorphism demonstrated here. In related studies employing fMRI, Okada et al (2010) report that responses in bilateral posterior superior temporal sulcus were sensitive to phonemic variability (intelligibility) of speech sounds, but not to acoustic variability.…”
Section: Discussionmentioning
confidence: 82%
“…While the novel sounds employed here varied only along three acoustic dimensions (one of which varied randomly), patterns of covariance naturally scale to high-dimensional feature spaces. In complex natural stimuli such as speech, multiple forms of stimulus attribute redundancy exist concurrently and successively (e.g., Delattre et al, 1955;Kluender et al, 2011;Lisker, 1978;Repp, 1982;Sussman et al, 1991Sussman et al, , 1998. To the extent that patterns of covariance among acoustic attributes in natural sounds are efficiently coded, these non-isomorphic representations may inform how the auditory system exploits different patterns of redundancy to learn to distinguish different speech sounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, another reasoning is that the articulatory link enables to define acoustic/auditory classes of equivalence, or to provide natural phonetic categories. Interestingly, these two different reasoning lead so different theoreticians as Liberman & Mattingly (1985) and Sussman et al (1998) to call for the same neuronal analogy in auditory processing: that is, the neuronal columns for auditory localisation in the inferior colliculus of the barn owl. Wagner et al (1987) or Konishi et al (1988) showed how different phase relations between the two ears, related to the same orientation in the 3D space (same azimuth) for tones of different frequencies, were organised within orientation dominance columns enabling to recover the invariant character of the distal event from the variable proximal stimulus.…”
Section: Iv2 Ingredients For a Computational Pact Architecturementioning
confidence: 99%
“…The biomechanical model was chosen because it has been shown to accurately account for articulatory trajectory shaping (Perrier et al 2003) and velocity profiles (Payan & Perrier 1997) in the mid-sagittal plane, all possibly important for consonant perception (Sussman et al 1998, Perrier & Fuchs 2008. Further, the model respects the relations between curvature and speed, which is found to be important in the correct perception of movements in general (Viviani & Stucchi 1992), and also for articulatory movements and thus speech (Perrier & Fuchs 2008).…”
Section: Modelling Physically Realistic Perceptual Stimulimentioning
confidence: 99%